Sweat sodium composition and sweat loss estimation through wearable sensors and predictive equations in dry and humid hot conditions - Bandiera, D.; de Bardonnèche, J.; Margout-Jantac, D.; Dubois, L.; Allaoui, N. E.; Rubio, J. S. E.; Aubin, J.-C.; Racinais, S.; Tessitore, A.; Pitsiladis, Y. (Frontiers in Physiology, 2025)
Introduction: Individualized sweat testing is essential for tailoring hydration and nutrition strategies, as water and sodium losses during exercise vary greatly across athletes. The validity of a wearable sweat sensor (S1, Flowbio) and a handheld analyzer (LAQUAtwin, Horiba Advanced Techno) for measuring sweat sodium concentration ([Na+]) was tested against flame photometry (FP). Additionally, whole body sweat loss (WBSL) estimated by the S1 and by a sweat rate calculator (SRC) was compared to the scale-based method.